Hybrid piezoelectric-triboelectric nanogenerators for flexible electronics: Recent advances and perspectives - Saichon Sriphan; Naratip Vittayakorn (Journal of Science Advanced Materials and Devices, 2022)
For several decades, a focus has been placed on the development of future flexible electronics, including electronic skin, wearable devices, environmental monitoring systems and the Internet of things (IoT) network. The triboelectric nanogenerator (TENG) attracted attention by developing this technology due to its high-performance, facile design/fabrication, light-weight and high flexibility. However, in some cases, the use of a pristine triboelectric material for a TENG operation might be insufficient for efficiently driving/sensing small-to-medium electronic systems without modification. Hence, a hybrid strategy between piezoelectric and triboelectric effects from piezoelectric nanogenerator (PENG) and TENG is proposed. This unique characteristic serves as a combination of polarized charges from the piezoelectricity and surface charges from the triboelectric effect when the hybrid device is subjected to mechanical stress. This provides a higher yield of charge density, which relates to a higher magnitude of output current. Through their outstanding performance, the hybrid PENG and TENG can be applied in various fields, especially in flexible electronics technology. Herein, an overview of recent advances for hybrid PENG and TENG developments is presented, including basic mechanisms, related theories, coupling effect, performance factors, and potential applications. The final part also discusses the challenges and perspectives for further development and the opportunity for the commercialization of this nanogenerator.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; Dielectric materials and actuators